Dissection of genetic basis underlying heat stress response of Apis cerana - Ao-Mei Li; Chun-Xiu Pang; Xiao-Lin Cai; Fu-Chang Zhuo; Bo Hu; Xue-Hua Huang; Jia-Xing Huang; Yu-Ming Lu (BMC Genomics)
Abstract The honeybee Apis cerana as an important pollinator contributes significantly to ecological diversity. In recent years, it has been used as a common pollinator in greenhouses, but it is highly susceptible to heat stress, which affects its behavior, physiology, survival, and gene expression. Here, we conducted transcriptomic analysis to identify differentially expressed genes (DEGs) and reveal the associated biological processes in the queen head and ovary of honeybee A. cerana under different temperatures. Differential expression analysis revealed 116 DEGs (72 upregulated, 44 downregulated) in the head and 106 DEGs (78 upregulated, 28 downregulated) in the ovary after 24 h of heat stress. At 96 h, 29 DEGs (17 upregulated, 12 downregulated) were identified in the head, and 44 DEGs (34 upregulated, 10 downregulated) in the ovary. After 168 h, the number of DEGs increased significantly: 846 DEGs (567 upregulated, 279 downregulated) in the head, 479 DEGs (296 upregulated, 183 downregulated) in the ovary, and 582 DEGs (338 upregulated, 244 downregulated) in the thorax. DEGs associated with metabolic processes, signaling, and transport pathways were significantly altered under heat stress, potentially contributing to the reduced reproductive and growth capacity of bees. Additionally, genes related to antioxidant activity, nutrient metabolism, heat shock proteins, zinc finger proteins, and serine/threonine-protein kinases were differentially expressed across treatments. Overall, the head and ovaries of honeybee queens show a significant response to heat shock, and these responses are related to antioxidant genes, heat shock proteins, and metabolic regulation, our findings provide genetic information for the breeding of heat-resistant bee strains.